Synthesis of a Progesterone-Carbachol Derivative: Relationship with Some Parameters Involved in its Geometry and Electronic Structure - Figueroa-Valverde, Lauro; Diaz-Cedillo, Francisco; Lopez-Ramos, Maria; Garcia-Cervera, Elodia; Pool-Gomez, Eduardo (Asian Journal of Chemistry, 2012)
In this study, a progesterone-carbachol (3) derivative was synthetized and its relationship with some physicochemical parameters involved in its geometry and electronic structure wasevaluated. The results showed an increase in the HOMO/LUMO, logP and p values of compound 3 with respect to progesterone. All this datasuggest that changes in the chemical structure of progesterone to form progesterone-carbacholexert variations in HOMO/LUMO, logP and p values.